Control of reduced electric field in the positive column of a pulsed discharge in CO₂ - Lisovskiy, V.A.; Dudin, S.V.; Vusyk, M.M.; Osmayev, R.O.; Yegorenkov, V.D.; Platonov, P.P. (Problems of Atomic Science and Technology, 2023)
The electric field strength in the positive column of dc and bipolar pulsed discharges in carbon dioxide was de-termined by the method of moving electrodes. It is shown that an increase in the frequency of the pulse voltage leads to the electric field strength increase. The following values of the reduced electric field E/p for a gas pressure of 0.5 Torr were obtained: 22.5 V/(cm·Torr) for dc discharge, 30 V/(cm·Torr) for pulsed discharge at 20 kHz for low-current mode and 32 V/(cm·Torr) for high-current mode, and 36.6 V/(cm·Torr) for 75 kHz. We see that in the dc discharge, the reduced electric field is weak, due to which the exchange of vibrational energy between CO₂ mole-cules dominates the conversion process. The increase of the electric field strength in the positive column of a pulsed discharge, especially under conditions of gas heating, allows obtaining E/N > 100 Td when the process of direct dissociation of CO₂ molecules by fast electrons makes the main contribution to the conversion process. Методом рухомих електродів була визначена величина напруженості електричного поля у позитивному стовпі розряду постійного струму та біполярних імпульсних розрядів у вуглекислому газі. Показано, що підвищення частоти імпульсної напруги призводить до збільшення напруженості електричного поля у позитивному стовпі. Були отримані наступні величини зведеного електричного поля E/p, коли тиск газу становив 0,5 Torr: для розряду постійного струму 22,5 В/(см·Toрр), так для імпульсного розряду з частотою 20 кГц значення зведеного електричного поля складало 30 В/(см·Toрр) для слабкострумового режиму та 32 В/(см·Toрр) для сильнострумового режиму і 36,6 В/(см·Toрр) для частоти 75 кГц. Бачимо, що у розряді постійного струму зведене електричного поле E/N слабке, завдяки чому обмін коливальною енергією між молекулами CO₂ домінує при процесі конверсії. Збільшення напруженості електричного поля у позитивному стовпі імпульсного розряду, особливо за умов нагріву газу, дозволяє отримати E/N > 100 Tд, коли процес прямої дисоціації молекул CO₂ швидкими електронами дає основний вклад у процес конверсії.